آلية توظيف أسلوب العينات غير الإحصائية في عملية الرقابة الشرعية في المؤسسات المالية الإسلامية The Mechanism of Employing The Method of Non-Statistical Samples in The Process of Sharia Supervision in Islamic Financial Institutions - Ali Hakami , Tahani; Obaid Hasan Saleh, Abdulmajid (International Journal of Al-Turath In Islamic Wealth and Finance, 2022)
يهدف البحث بشكل رئيس إلى تمكين المؤسسات المالية الإسلامية من استخدام اسلوب العينات غير الإحصائية في عمليات المراجعة والرقابة الشرعية لديها من خلال تقديم معرفة متكاملة عن اسلوب العينات غير الإحصائية وتكييفها مع مبادئ الشريعة الإسلامية. يسعى البحث إلى الإجابة عن سؤال رئيسي وهو: كيف يمكن توظيف اسلوب العينات غير الإحصائية في الرقابة الشرعية في المؤسسات المالية الإسلامية؟ يتبع البحث المنهجي النوعي من خلال تحليل محتوى الدراسات السابقة المتعلقة بموضوع البحث للإجابة على تساؤل البحث الرئيس. توصلت الدراسة إلى نتائج من أهمها: لتطبيق اسلوب العينة في عملية الرقابة الشرعية لا بد من توفر عناصر مثل: موارد بشرية مؤهلة شرعياً ومهنياً، توفر مرجعية شرعية، الفصل بين المصالح المتعارضة محاسبياً وإدارياً وشرعياً، توفر فريق تدقيق شرعي داخلي. هناك عدة تقارير تصدر عن المراجع الشرعي مثل: تقارير الزيارة الميدانية، تقارير المتابعة، التقرير الختامي، حيث توضح مدى التزام المصارف بأحكام الشريعة الإسلامية فيما يتعلق بالمعاملات المالية. ينتج عن العينات الإيجابية أثاراً شرعية تؤكد سلامة سياسات واجراءات المصارف الإسلامية في تعاملاتها المالية مع المستفيدين، ويمكن توضيح الآثار الشرعية المترتبة على العينات الإيجابية بما يلي: اثبات حِل الأرباح المعاملات المالية، اثبات وجوب إخراج الزكاة، الحكم على باقي المعاملات المالية وفق العينة الإيجابية بأنها خالية من المخالفات الشرعية، اصدار التقرير الشرعي النظيف يبين أن التعاملات المالية للمصرف تتفق وأحكام الشريعة الإسلامية، اثبات نسبة العينة أو تقليل حجمها. Abstract The research aims mainly to enable Islamic financial institutions to use the non-statistical sampling method in their Shariah audit and supervision processes by providing integrated knowledge of the non-statistical sampling method and adapting it to the principles of Islamic Sharia. The research seeks to answer a main question: How can the non-statistical sampling method be employed in Shariah supervision in Islamic financial institutions? The qualitative methodological research is followed by analyzing the content of previous studies related to the research topic to answer the main research question. The study reached results, the most important of which are: To apply the sampling method in the Shari’a control process, elements such as: legally and professionally qualified human resources, availability of a legitimate reference, separation of conflicting interests accounting, administratively and legally, the availability of an internal Shari’a audit team. There are several reports issued by Sharia auditors, such as: field visit reports, follow-up reports, and the final report, which show the extent to which banks comply with the provisions of Islamic Sharia in relation to financial transactions. Positive samples result in legitimate effects that confirm the integrity of the policies and procedures of Islamic banks in their financial dealings with the beneficiaries, and the legitimate effects of positive samples can be clarified by the following: Proving the solution to profit financial transactions, proving that Zakat must be paid, judging the rest of the financial transactions according to the positive sample that they are free of Shari’a violations, issuing a clean Shari’a report showing that the bank’s financial transactions are in accordance with the provisions of Islamic Shari’a, proving the percentage of the sample or reducing its size.